Decandrinin, an unprecedented C9-spiro-fused 7,8-seco-ent-abietane from the Godavari mangrove Ceriops decandra - Wang, Hui; Li, Min-Yi; Katele, Félix Zongwe; Satyanandamurty, Tirumani; Wu, Jun; Bringmann, Gerhard (Beilstein Journal of Organic Chemistry, 2014)
Decandrinin (1), an unprecedented C9-spiro-fused 7,8-seco-ent-abietane, was obtained from the bark of an Indian mangrove, Ceriops decandra, collected in the estuary of Godavari, Andhra Pradesh. The constitution and the relative configuration of 1 were determined by HRMS (ESI) and extensive NMR investigations, and the absolute configuration by circular dichroism (CD) and optical-rotatory dispersion (ORD) spectroscopy in combination with quantum-chemical calculations. Decandrinin is the first 7,8-seco-ent-abietane.
Keywords: abietane; absolute configuration; Ceriops decandra; circular dichroism; decandrinin; Rhizophoraceae